Modeling of traffic of computer networks in base of tensor orthogonal - Мінаєв, Ю. М.; Філімонова, О. Ю. (Problems of Informatization and Control, 2005)
The questions of modeling of traffic of computer networks by presentations traffic in the manner of the tensor of second rank are discussed. Shown that using the orthogonal invariants of tensor allows practically uniquely identify condition to computer network, in particular, reveal presence of anomalous conditions